2021
DOI: 10.1039/d0cp05745b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Fermi resonances in the complex vibrational spectra of the methyl groups in methylamines

Abstract: Vibrational spectra of the methyl groups in mono-methylamine (MMA), dimethylamine (DMA), and trimethylamine (TMA) monomers and their clusters were measured to capture their spectral features as a result of bend/umbrella-stretch Fermi resonance (FR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In the latter group, the frequency of umbrella modes is close to the bending modes and CH stretching fundamental has red‐shifted, both factors result in better energy‐matching conditions that give rise to more complex vibrational features between 2800 and 3000 cm −1 . It is also worth mentioning that the FR patterns in CH 3 OH/CH 3 OCH 3 are similar to their counterparts in MMA, DMA, and TMA [ 20 ] with main difference in the position and intensity of the three CH stretching fundamentals.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In the latter group, the frequency of umbrella modes is close to the bending modes and CH stretching fundamental has red‐shifted, both factors result in better energy‐matching conditions that give rise to more complex vibrational features between 2800 and 3000 cm −1 . It is also worth mentioning that the FR patterns in CH 3 OH/CH 3 OCH 3 are similar to their counterparts in MMA, DMA, and TMA [ 20 ] with main difference in the position and intensity of the three CH stretching fundamentals.…”
Section: Discussionmentioning
confidence: 75%
“…Our spectrum is broadened by the rotational profile, which is similar to an early work on MMA monomer. [ 20 ] Bernstein and coworkers have identified four bands at 3010, 2956, 2925, and 2837 cm −1 and assigned them to be ν 2 , ν 9 , combination/overtone state, and ν 3 , respectively. Vibrational spectrum of CH 3 OCH 3 , measured in this study, is shown in Figure 2d in which four well‐resolved groups of peaks at 2816, 2880, 2922, and 2998 can be seen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] F-R is later observed in the C═O stretching vibration of ketone [2] and in the X H stretching vibration, where X refers mostly to O, N, and C atom. [3][4][5][6][7][8][9][10] Sibert and coworkers analyzed the F-R between C H stretching and overtone C H bending vibrations of alkyl group by model Hamiltonian based on scaled frequencies obtained from DFT calculations. [4] For the larger molecules, Roy et al applied the vibrational self-consistent field with second-order perturbation correction (VSCF-PT2) algorithm with HF/MP2 potentials to analyze the vibrational spectra of N-acetyl tryptophan amide and its derivative with an extended peptide backbone.…”
Section: Introductionmentioning
confidence: 99%